VD_FINDINFO HC / 2012 / 470 vom 27. Juni 2012 - VD Tribunal cantonal (2012)
CAMPING, BAIL À LOYER, DÉFAUT DE LA CHOSE, DISTANCE À LA LIMITE, DOMMAGES-INTÉRÊTS, CIRCONSTANCE EXTRAORDINAIRE | 259a al. 1 CO, 259e CO, 153 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 36 al. 1 LCCR, 36 al. 2 LCCR